High-entropy RuO2 catalyst with dual-site oxide path for durable acidic oxygen evolution reaction - Fangren Qian; Dengfeng Cao; Shuangming Chen; Yalong Yuan; Kai Chen; Peter Joseph Chimtali; Hengjie Liu; Wei Jiang; Beibei Sheng; Luocai Yi; Jiabao Huang; Chengsi Hu; et al. (Nature Communications)
Abstract Developing durable acidic oxygen evolution reaction catalysts is critical for industrial proton exchange membrane water electrolyzers. We incorporate high-entropy atoms (Co, Ni, Cu, Mn, Sm) into RuO2 (RuO2-HEAE) via annealing, achieving remarkably high stability (>1500 h at 100 mA cm− 2). In situ differential electrochemical mass spectrometry and operando Attenuated Total Reflection Surface-Enhanced Infrared Absorption Spectroscopy reveal RuO2-HEAE follows a dual-site oxide path mechanism instead of the conventional adsorbate evolution mechanism. Quantitative Fourier-transformed extended X-ray absorption fine structure fitting and density functional theory calculations show this mechanistic shift stems from an elongated Ru-M distance in second coordination shell of RuO2-HEAE, enabling direct O-O coupling. This OPM-type catalyst delivers ~1500 h of stable operation at 1 A cm− 2 and 50 °C, demonstrating superior durability versus most reported RuO2-based catalysts. This work provides fundamental insights for designing highly stable proton exchange membrane water electrolysis.